Paytm : navigating the transition from an e-wallet to a payments bank - Sahay, Arvind; Tiwari, Tara (London : Indian Institute of Management, Ahmedabad, 2019)
The case centres around the challenges faced by Paytm, India's largest e-wallet, in its transition from a mobile wallet to a payments bank. The shift was the result of a push by Reserve Bank of India (RBI), the central bank of India and regulator of the banking system, in 2015, pending the approval of the new Payments Bill. The transition from Paytm mobile wallet to Paytm Payments Bank had added to the complexity of business for Paytm. Paytm Payments Bank had a target to increase its customer base from 180 million to 500 million by 2020.
Originally Published InSahay, A., & Tiwari, T. (2019). Paytm: Navigating the Transition from an E-Wallet to a Payments Bank. IIMA/MAR0501. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Internet banking -- India -- Case studies